Contracting relationships between donors and care providers:: a future-proof reform - SALMI , Madjid (Journal of Human Sciences, 2022)
The health system requires colossal financial resources for its reproduction.  However, social security is confined to financing health structures without being granted any right of supervision over the activities of the latter. Our main question is the following: can social security continue indefinitely, as in the past, to finance health care structures or rather the activities that the latter will have to develop? Our hypotheses are: contractualisation at these different levels (internal/external) will strengthen social security in its financing of health care institutions' activities. The results obtained concluded that the contractualisation of relations between funding bodies and health care institutions must be accompanied by an institutional project supported by adequate material, financial and human resources.